2019
DOI: 10.3390/pr7080541
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a High-Pressure Submerged Jet Using a Cavitation Model Considering Effects of Shear Stress

Abstract: In the current research, a high-pressure submerged cavitation jet is investigated numerically. A cavitation model is created considering the effect of shear stress on cavitation formation. As such, this model is developed to predict the cavitation jet, and then the numerical results are validated by high-speed photography experiment. The turbulence viscosity of the renormalization group (RNG) k-ε turbulence model is used to provide a flow field for the cavitation model. Furthermore, this model is modified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It can be seen that in the first two cases, the cavitation zone propagated through the entire domain, and in the last case it propagated up to 87 mm; therefore, this nozzle can effectively produce cavitation in well depths up to 300 m. It is also shown that cavitation clouds are formed inside the nozzle; they continue developing downstream and then expand. The experimental results presented in [21] demonstrate that cavitation jets consist of three zones: growing, shedding and collapsing. When a cavitation cloud propagating from a nozzle reaches a specific location, the downstream part is shed from the initial cloud.…”
Section: Numerical Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It can be seen that in the first two cases, the cavitation zone propagated through the entire domain, and in the last case it propagated up to 87 mm; therefore, this nozzle can effectively produce cavitation in well depths up to 300 m. It is also shown that cavitation clouds are formed inside the nozzle; they continue developing downstream and then expand. The experimental results presented in [21] demonstrate that cavitation jets consist of three zones: growing, shedding and collapsing. When a cavitation cloud propagating from a nozzle reaches a specific location, the downstream part is shed from the initial cloud.…”
Section: Numerical Resultsmentioning
confidence: 89%
“…It was developed using re-normalization group (RNG) methods to re-normalize the Navier-Stokes equations in order to consider the effects of smaller scales in the flow [20]. Such a model was successfully used in [21] for the dynamic study of cavitation jets. The Autodesk CFD package was used for numerical modelling.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Recently, Yang et al [33] compared their numerical predictions of the cavitation cloud in a cavitating jet to their high-speed flow visualizations. They found almost zero vapor volume fraction in the central region of the jet near the nozzle exit and the presence of a ring-type cavitation zone in the high-speed shear layer, around the central zone.…”
Section: Cavitating Jet Flow Dynamicsmentioning
confidence: 99%
“…Yang et al [33] also studied the effect of the diverging angle of the nozzle exit on the flow dynamics using the RANS RNG k-ε turbulence model. The vapor volume fraction distribution showed (Figure 4) that the cavitation cloud is larger for a 60 • angle than for 40 • and 80 • .…”
Section: Cavitating Jet Flow Dynamicsmentioning
confidence: 99%
“…Fig. 1 shows the high-pressure cavitation jet experiment system, which is mentioned in our former works [20]. The system uses an Italian ANNOVI REVERBERI SHP 15.50N high-pressure piston pump to provide high pressure for the jet.…”
Section: Introductionmentioning
confidence: 99%